2015
DOI: 10.1002/smll.201403508
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ultrathin Bi2S3 Nanosheets for High‐Performance, Flexible, Visible–NIR Photodetectors

Abstract: Ultrathin Bi2 S3 nanosheets with thicknesses down to 2.2 nm are fabricated. The resultant ultrathin Bi2 S3 -based photoconductor shows high sensitivity to visible-near infrared light from 405 to 780 nm with a high external photoresponsivity up to 4.4 A W(-1) , high detectivity of ≈10(11) Jones, relatively fast response time of ≈10 μs, and high flexibility and durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
139
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(147 citation statements)
references
References 60 publications
5
139
0
Order By: Relevance
“…2D materials such as graphene, hexagonal boron nitride (h‐BN), VS 2 , Bi 2 S 3 , and GaSe have been widely studied, because of their great potential in the field of catalysis, microelectronics, ion storage, and optoelectronics 1, 2, 3, 4, 5, 6, 7, 8, 9, 10. As one of the most significant members of 2D materials family, transition metal dichalcogenides (TMDs), such as MoS 2 , MoSe 2 , WS 2 , and WSe 2 , have attracted tremendous attention currently due to their outstanding electronic, optical, and mechanical properties 11, 12, 13, 14, 15, 16, 17, 18, 19.…”
mentioning
confidence: 99%
“…2D materials such as graphene, hexagonal boron nitride (h‐BN), VS 2 , Bi 2 S 3 , and GaSe have been widely studied, because of their great potential in the field of catalysis, microelectronics, ion storage, and optoelectronics 1, 2, 3, 4, 5, 6, 7, 8, 9, 10. As one of the most significant members of 2D materials family, transition metal dichalcogenides (TMDs), such as MoS 2 , MoSe 2 , WS 2 , and WSe 2 , have attracted tremendous attention currently due to their outstanding electronic, optical, and mechanical properties 11, 12, 13, 14, 15, 16, 17, 18, 19.…”
mentioning
confidence: 99%
“…Upon the excitation of light, the bound electron-hole pairs are generated by the incident photons whose energy is greater than the band gap of the semiconductor and the yielded photocurrent is correlated with light intensity [15]. Compared to silicon with an indirect band gap or graphene without a band gap [59], NB2DMs with tunable direct band gap and high absorption efficiency have emerged as potential candidates for next-generation flexible photodetectors [22,[71][72][73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Photodetectorsmentioning
confidence: 99%
“…In addition, the presence of a band gap and the high degree of electrostatic control could induce to a low dark current, which makes the monolayer MoS 2 -based photodetectors can be turned off. However, the devices suffered an intrinsic limitation of slow photoresponse dynamics and the resulted response time is long as 4 s. Chen et al [73] reported the study of flexible photodetectors based on ultrathin Bi 2 S 3 nanosheets (Fig. 5c) and the devices exhibited relatively fast response time as 10 μs (Fig.…”
Section: Photodetectorsmentioning
confidence: 99%
“…With a direct narrow band gap of around 1.3 eV, bismuth sulfide (Bi 2 S 3 ), emerging as one promising member of group V-VI binary semi-conductors, has been attracting considerable attention due to its wide range of application in the field of solar cells [8,9], photo-detectors [10][11][12][13][14], gas sensors [14], thermoelectric devices [15], X-ray computed tomography imaging [16], lithium-ion batteries [17][18][19][20], and photocatalysis [21][22][23]. Bi 2 S 3 micro/nanostructures with various morphologies, including one-dimensional (1D) nanorods/nanowires, two-dimensional (2D) nanosheets/flakes, and three-dimensional (3D) hierarchical complex architectures, have been successfully fabricated in previous studies [10][11][12][13][14][15][17][18][19][23][24][25][26], since the properties of functional nanostructured materials are strongly dependent on the tailored morphology, microstructure and surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…Bi 2 S 3 micro/nanostructures with various morphologies, including one-dimensional (1D) nanorods/nanowires, two-dimensional (2D) nanosheets/flakes, and three-dimensional (3D) hierarchical complex architectures, have been successfully fabricated in previous studies [10][11][12][13][14][15][17][18][19][23][24][25][26], since the properties of functional nanostructured materials are strongly dependent on the tailored morphology, microstructure and surface properties. Among them, 3D hierarchical complex architectures have exhibited excellent properties for applications in gas sensors, lithium batteries, and photocatalysts due to their large surface area and facile electron (ion) transport.…”
Section: Introductionmentioning
confidence: 99%